Electrocatalysis of oxygen reduction reaction on mesoporous TiO2, In2O3 and TiO2 – In2O3 films - Maltanava, Hanna M.; Gaevskaya, Tatiana V.; Kurenkova, Anna Yu.; Saraev, Andrey A.; Poznyak, Sergey K. (Journal of the Belarusian State University. Chemistry, 2026)
Films of individual oxides TiO2, In2O3 and TiO2 – In2O3 composites have been obtained from sols via spin-coating technique with subsequent annealing at 200 and 450 °C. Using scanning electron microscopy, transmission electron microscopy and Raman spectroscopy, it was established that the samples after annealing have a mesoporous structure with a disordered pore distribution and consist of TiO2 and In2O3 nanocrystallites 5–15 nm in size. During the study of the electrochemical activity of the obtained films in the oxygen reduction reaction in an alkaline medium using the cyclic voltammetry method, it was revealed that the efficiency of the oxygen reduction reaction on TiO2, In2O3 and TiO2 – In2O3 electrodes is determined by the nature of the oxide, the TiO2 and In2O3 ratio in composite systems, as well as the film surface condition and the size of the oxide nanocrystallites, which affect the transport of charge carriers from the substrate through the oxide layer to the adsorbed reagents from the solution.
Keywords: titanium dioxide; indium(III) oxide; composite; film; electrocatalysis; oxygen reduction